AB1456-HPR Where the needs of mothers with rheumatoid arthritis meet arthritis-related health care. (23rd January 2014) - Prodinger, B.; Shaw, L.; Laliberte-Rudman, D.; Stamm, T.
Abstract : Background: People with rheumatoid arthritis (RA) are provided comprehensive health care most commonly in institutionalized settings. Critique has been raised that such settings are organized primarily to treat illness and disease-related symptoms of people rather than maintaining and promoting people's health and full participation in their daily lives. Inadequacy in addressing particularly women's health issues has also been described. Objectives: The aim of this study was to understand how Austrian mothers with RA manage their everyday lives and how their needs are attended in arthritis-related health care in Austria. Methods: An institutional ethnographic study was conducted. Seven Austrian mothers with RA, aged between 28 and 41, and varying working and living conditions (being on maternity leave, part-time employment, social assistance and invalidity pension recipient) were recruited. Data collection included interviews and participation observations. Women's health care records were included into analysis as they are exemplary for the interaction between the patient and health care over time. Institutional ethnographic analysis comprised first inductive reading of the data to understand what the women are actually doing in their daily lives; an analysis of the hospital records to understand the organization of and relations within arthritis-related health care in an outpatient rheumatology department; and consequently an analysis of how women's daily lives are met within these relations was explored. Results: The ethnographic account of this study reveals how participants try to satisfy and meet the needs of their families, put effort into maintaining paid employment and continuing (outdoor-) activities with family and friends, engage in informal caregiving for their children and significant others, while also integrate their disease-related symptoms. Given the multiple demands due to family and work, the women highlighted that challenges in daily life are not necessarily due to disease-related symptoms or limitations in performing a particular task, but in the coordination of multiple tasks simultaneously as they unfold throughout the entire day. The analysis of the documents revealed that arthritis-related health care is ruled by relations based on biomedical concepts that focus predominantly on disease parameters and measurable, objectifiable dimensions of people's functioning. The complexity of participants' daily life remains likely unattended in specialized arthritis-related health care as its multidimensionality cannot be easily reduced into distinct measurable concepts and outcomes. Conclusions: This study underscores the importance of interdisciplinary treatment in specialized arthritis-related health care based on a comprehensive understanding of and attendance to how the disease might affect people's health and participation in daily life. Disclosure of Interest: None Declared